The Legislative Effects of Campaign Personalization An Analysis on the Legislative Behavior of Successful German Constituency Candidates. (February 2021) - Zittel, Thomas; Nyhuis, Dominic
Personalized campaign styles are of increasing importance in contemporary election campaigns at all levels of politics. Surprisingly, we know little about their implications for the behavior of successful candidates once they take public office. This paper aims to fill this gap in empirical and theoretical ways. It shows that campaign personalization results in legislative personalization. Legislators that ran personalized campaigns are found to be more likely to deviate in roll call votes and to take independent positions on the floor. These findings result from a novel dataset that matches survey evidence on candidates' campaign styles in the 2009 German Federal Elections with the legislative behavior of successful candidates in the 17th German Bundestag (2009–2013). Combining data from the campaign and legislative arenas allows us to explore the wider consequences of campaign personalization.